Chemoselective Activation of Diethyl Phosphonates: Modular Synthesis of Biologically Relevant Phosphonylated Scaffolds. Issue 40 (11th September 2018) - Adler, Pauline; Pons, Amandine; Li, Jing; Heider, Jörg; Brutiu, Bogdan R.; Maulide, Nuno
Abstract: Phosphonates have garnered considerable attention for years owing to both their singular biological properties and their synthetic potential. State‐of‐the‐art methods for the preparation of mixed phosphonates, phosphonamidates, phosphonothioates, and phosphinates rely on harsh and poorly selective reaction conditions. We report herein a mild method for the modular preparation of phosphonylated derivatives, several of which exhibit interesting biological activities, that is based on chemoselective activation with triflic anhydride. This procedure enables flexible and even iterative substitution with a broad range of O, S, N, and C nucleophiles. Abstract : One module at a time : A mild method for the modular preparation of phosphonylated derivatives, several of which exhibit interesting biological activities, is based on chemoselective activation with triflic anhydride. This procedure enables flexible and even iterative substitution with a broad range of O, S, N, and C nucleophiles.